2018
DOI: 10.1007/s10067-018-3982-9
|View full text |Cite
|
Sign up to set email alerts
|

Biosimilars in rheumatology: recommendations for regulation and use in Middle Eastern countries

Abstract: The increasing availability of biosimilar medicines in Middle Eastern regions may provide an opportunity to increase the number of rheumatology patients who have access to traditionally more expensive biologic medicines. However, as well as a lack of real-world data on the use of biosimilar medicines in practice, the availability of intended copies in the region may undermine physician confidence in prescribing legitimate biosimilar medicines. There is a need for regional recommendations for healthcare profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 39 publications
1
32
0
1
Order By: Relevance
“…To monitor AEs and to attribute them to the correct product, improved pharmacovigilance efforts are still largely needed in the era of biosimilars, although some advances have been made [ 77 ]. Accordingly, a number of medical societies have proposed requirements for postmarketing surveillance, registries, and traceability [ 30 , 32 , 33 , 78 , 79 ].…”
Section: Challenges With Multiple Switchingmentioning
confidence: 99%
“…To monitor AEs and to attribute them to the correct product, improved pharmacovigilance efforts are still largely needed in the era of biosimilars, although some advances have been made [ 77 ]. Accordingly, a number of medical societies have proposed requirements for postmarketing surveillance, registries, and traceability [ 30 , 32 , 33 , 78 , 79 ].…”
Section: Challenges With Multiple Switchingmentioning
confidence: 99%
“…Although many countries in the Middle East do not have biosimilar guidelines, several countries, including Iran, Lebanon, and Saudi Arabia, have developed guidelines 42. The Iran National Regulatory Authority used the WHO biosimilar guidelines as a resource; however, the Iranian guidelines are not as strict.…”
Section: Methodsmentioning
confidence: 99%
“…According to the most recent information available, three biologic therapies that are used in rheumatology are approved in Iraq: the TNF inhibitors etanercept and infliximab, and the anti-CD20 monoclonal antibody, rituximab 48. Only the originator biologics are available; no biosimilars are approved in the country 16,42…”
Section: Methodsmentioning
confidence: 99%
“…In the USA, on average, 40% of RD patients receive biological treatment, in contrast to the Middle East and north Africa where coverage is only 2% [ 33 , 63 ]. The factors considered for this inequality may be associated with the difficult access of BP and with the difficulties in monitoring treatment with biologicals.…”
Section: Biopharmaceuticals In Rheumatic Diseasesmentioning
confidence: 99%
“…According to the FDA, in the Biologics Price Competition and Innovation Act (BPCIA) of 2009, manufacturers must supply sufficient information to indicate the biosimilarity of the biotherapeutic, including the same clinical result as the reference product in any patient. Equally, if there is a change from an innovator to a biosimilar, it must be demonstrated that the administration of the biosimilar will not affect the safety and efficacy of the innovator [ 63 , 65 , 66 ].…”
Section: Biopharmaceuticals In Rheumatic Diseasesmentioning
confidence: 99%